Studi Analisis Tentang Pembelajaran Soft Skills Oleh Guru Terhadap Siswa Program Studi Keahlian Teknik Gambar Bangunan SMK Negeri 1 Jakarta - Hikmawati Hikmawati (LPPM Universitas Negeri Jakarta, 2014)
The objectives of this study analyzing the relationship between students learning achievement in the classroom and students of furniture engineering’s practice achievement. This study was conducted in SMKN 4 Jakarta, the population of this study were the year XI students which specialized in Furniture Engineering Competences and wood construction engineering, year 2012/2013 which consist of 18 students. The number of the sample is 12 students. The problem which the writer got from this study was that the students learning achievement was in proportion to the practice achievement, dan the oppositeThe instrument of this study is a test which is used to know the relation between students’ learning achievements in the classroom and the students’ practice achievement. The quesioner shows that the data were valid and the reability was high with r11 = 0.8793, with 30 point of questions (20 multiple choice questions and 10 essay questions). The result of the study showed that students’ learning achievements average score was 76.7 and students practice achievement average score was 78.67.It showed that the practice has a positive relationship (0.942). In other words, students’ learning achievement give contributions to the percentage of practice ability. The students have to prepare themselves to be focus to the lesson or material from the teacher and the teacher should prepare the material and better learning method to help the students to be able to receive all the materials.